PENGEMBANGAN INTEGRATED MONITORING SYSTEM BERBASIS INTERNET OF THINGS (IOT) PADA KENDARAAN STEYR 91 ROSENBAUER - Muhamad Akmal Hibban; Togi Adnan Maruli Sinaga; Emilia Rahajeng Larasati (LPPM Politeknik Pratama Kendal, 2025)
Aviation safety is a top priority in the aviation industry, including airport rescue and fire fighting training activities in vocational education institutions such as the Indonesian Aviation Polytechnic Curug (PPIC). The Steyr 91 Rosenbauer training vehicle used in firefighting simulations still relies on analog indicators to monitor water levels in the tank, which are often inaccurate and disrupt training operations. To address this issue, this research developed an Internet of Things (IoT)-based Integrated Monitoring System capable of monitoring water levels in real time, both locally through OLED and LED/Buzzer indicators, and remotely via an IoT Cloud dashboard. The system utilizes the JSN-SR04M ultrasonic sensor and ESP32 microcontroller designed to operate independently, efficiently, and responsively under critical conditions. The research method applied is Research and Development (R&D) level 3 with validation and effectiveness testing. The test results show that the system functions accurately and provides effective early warnings. This innovation is expected to improve training efficiency and safety in ARFF (Airport Rescue and Fire Fighting) and serve as a technological model adaptable for other firefighting vehicles.